Ambulatory Blood Pressure Trajectory and Perceived Stress in Relation to Birth Outcomes in Healthy Pregnant Adolescents. Issue 5 (June 2019) - Spicer, Julie; Giesbrecht, Gerald F.; Aboelela, Sally; Lee, Seonjoo; Liu, Grace; Monk, Catherine
ABSTRACT: Objective: An early decline in resting blood pressure (BP), followed by an upward climb, is well documented and indicative of a healthy pregnancy course. Although BP is considered both an effector of stress and a clinically meaningful measurement in pregnancy, little is known about its trajectory in association with birth outcomes compared with other stress effectors. The current prospective longitudinal study examined BP trajectory and perceived stress in association with birth outcomes (gestational age (GA) at birth and birth weight (BW) percentile corrected for GA) in pregnant adolescents, a group at risk for stress-associated poor birth outcomes. Methods: Healthy pregnant nulliparous adolescents ( n = 139) were followed from early pregnancy through birth. At three time points (13–16, 24–27, and 34–37 gestational weeks ±1 week), the Perceived Stress Scale was collected along with 24-hour ambulatory BP (systolic and diastolic) and electronic diary reporting of posture. GA at birth and BW were abstracted from medical records. Results: After adjustment for posture and pre-pregnancy body mass index, hierarchical mixed-model linear regression showed the expected early decline ( B = −0.18, p = .023) and then increase ( B = 0.01, p < .001) of diastolic BP approximating a U-shape; however, systolic BP displayed only an increase ( B = 0.01, p = .010). In addition, the models indicated a stronger systolic and diastolic BP U-shape for early GA at birth and lower BW percentile and an inverted U-shape for late GA at birth and higher BW percentile. No effects of perceived stress were observed. Conclusions: These results replicate the pregnancy BP trajectory from previous studies of adults and indicate that the degree to which the trajectory emerges in adolescence may be associated with variation in birth outcomes, with a moderate U-shape indicating the healthiest outcomes.